2012
DOI: 10.1037/a0028442
|View full text |Cite
|
Sign up to set email alerts
|

Necessity is the mother of invention: Avoidance motivation stimulates creativity through cognitive effort.

Abstract: Compared with approach motivation, avoidance motivation has often been related to reduced creativity because it evokes a relatively inflexible processing style. This finding seems inconsistent with the dual pathway to creativity model, which poses that both flexible and persistent processing styles can result in creative output. Reconciling these inconsistencies, the authors hypothesized that avoidance-motivated individuals are not unable to be creative, but they have to compensate for their inflexible process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
206
2
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(220 citation statements)
references
References 92 publications
8
206
2
4
Order By: Relevance
“…Retaining novel information in creative thinking and discriminating between task-relevant and task-irrelevant information are two crucial WM processes (Unsworth & Engle, 2007); therefore, WM capacity is essential to creative thinking. The empirical study conducted by De Dreu et al(2012) reported that when participants were asked to complete each RAT item, they were also asked to remember two (low load) or five (high load) digit strings. After completing the RAT items, the participants were required to recall all the strings.…”
Section: Overinclusive Thinking Trainingmentioning
confidence: 99%
“…Retaining novel information in creative thinking and discriminating between task-relevant and task-irrelevant information are two crucial WM processes (Unsworth & Engle, 2007); therefore, WM capacity is essential to creative thinking. The empirical study conducted by De Dreu et al(2012) reported that when participants were asked to complete each RAT item, they were also asked to remember two (low load) or five (high load) digit strings. After completing the RAT items, the participants were required to recall all the strings.…”
Section: Overinclusive Thinking Trainingmentioning
confidence: 99%
“…That is the reason why emotional aspect is a constituent in the linear/nonlinear thinking construct. Moreover, goal orientation has been proposed as a moderator of the effects of mood on creativity (De Dreu, Baas & Nijstad, 2008;Roskes, De Dreu & Nijstad, 2012). Similarly, imagination on one hand constitutes a facilitator of linear thinking (reproductive imagination) and on the other hand, it is focused on mental processes within an inner world (creative imagination) (e.g.…”
Section: Edwards-schachter Et Al (2015)mentioning
confidence: 99%
“…We focus on cognitive persistence as the underlying mechanism, because the literature on creativity has documented how this variable accounts for creativity in the context of unfulfilled goals (De Dreu et al, 2008Dietrich, 2004;Evans, 2003;Finke, 1996;Sagiv, Arieli, Goldenberg, & Goldschmidt, 2010;Simonton, 1997). An unfulfilled goal activates a mental process that enables individuals to block distracting thoughts, thereby concentrating intensely on the task at hand and exploring a smaller number of categories in depth to fully understand the problematic situation (Dreisbach & Goschke, 2004;Koch, Holland, & Van Knippenberg, 2008;Roskes et al, 2012). By enabling this concerted focus on a situation, and a systematic exploration of associated problems, cognitive persistence fosters creativity.…”
Section: Effects Of Relationship Conflict and The Relational Self On mentioning
confidence: 99%
“…Engaging in in-depth and detailed thinking (cognitive persistence) is not necessarily synonymous with deriving the most appropriate solution (convergent thinking) or generating diverse ideas (divergent thinking). However, cognitive persistence is a precursor of convergent and divergent thinking and, thus, of creativity: The more thoroughly and deeply people think, the more they are likely to generate appropriate solutions or diverse ideas, demonstrating greater creativity (Boden, 1998;De Dreu et al, 2008Dietrich, 2004;Finke, 1996;Roskes et al, 2012;Simonton, 1997).…”
Section: Effects Of Relationship Conflict and The Relational Self On mentioning
confidence: 99%
See 1 more Smart Citation